Breast cancer detection and tumor characteristics in BRCA1 and BRCA2 mutation carriers - Krammer, Julia (Breast cancer research and treatment, 2017)
PurposeTo describe imaging findings, detection rates, and tumor characteristics of breast cancers in a large series of patients with BRCA1 and BRCA2 mutations to potentially streamline screening strategies.MethodsAn IRB-approved, HIPAA-compliant retrospective analysis of 496 BRCA mutation carriers diagnosed with breast carcinoma from 1999 to 2013 was performed. Institutional database and electronic medical records were reviewed for mammography and MRI imaging. Patient and tumor characteristics including age at diagnosis, tumor histology, grade, receptor, and nodal status were recorded.ResultsTumors in BRCA1 mutation carriers were associated exhibited significantly higher nuclear and histological grade compared to BRCA2 (p < 0.001). Triple-negative tumors were more frequent in BRCA1 mutation carriers, whereas hormone receptor-positive tumors were more frequent in BRCA2 mutation carriers (p < 0.001). BRCA2 mutation carriers more frequently presented with ductal carcinoma in situ (DCIS) alone 14% (35/246) and cancers more frequently exhibiting calcifications (p < 0.001). Mammography detected fewer cancers in BRCA1 mutation carriers compared to BRCA2 (p = 0.04): 81% (186/231) BRCA1 versus 89% (212/237) BRCA2. MRI detected 99% cancers in each group. Mammography detected cancer in two patients with false-negative MRI (1 invasive cancer, 1 DCIS). Detection rates on both mammography and MRI did not significantly differ for women over 40 years and women below 40 years.ConclusionsBreast cancers in BRCA1 mutation carriers are associated with more aggressive tumor characteristics compared to BRCA2 and are less well seen on mammography. Mammography rarely identified cancers not visible on MRI. Thus, the omission of mammography in BRCA1 mutation carriers screened with MRI can be considered.